Basil I’s Path to Power according to the Vita Basilii as a Heroic Myth - Kubicki, Łukasz (Studia Ceranea, 2023)
This paper aims to illustrate how the tradition of Basil I’s rise to power in the Vita Basilii includes elements typical of heroic myths, according to Joseph Campbell’s monomyth scheme. The study presented here will examine how the narrative contains features such as a call to adventure, a series of trials and a motive for return. Moreover, the study seeks to investigate how these universal elements of hero stories have been mythicised by literary devices such as the topoi, text composition, intertextual references or symbolic content coherent with the perception of the ideological role of the Byzantine rulers. Within this framework, the study will aim to explore the morphology of these narratives and reconsider some historical questions with the help of Mircea Eliade’s theory of myth. It will focus on the identity and legitimising functions of the story for Constantine VII Porphyrogenitus and assess its impact on the position of the Macedonian dynasty in the social order and the sphere of political activity.